The absence or presence of Distance Education in contemporary public policies for the initial training of Basic Education teachers - Will, Daniela Erani Monteiro (2020)
This article analyzes relevant aspects to the understanding of the presence or absence of Distance Education in current public policies in the contemporary world. The focus of this study includes from the National Conference on Education - 2010 to the National Curriculum Guidelines for the training of Basic Education teachers - 2019. As methodological procedure, we adopted the documentary analysis of legal texts and dialogues with Dourado, Barreto, Mill and Minto for considerations on the distance education movement in teacher training. We concluded that despite resistance and mobilizations for the demarcation and implementation of distance education in higher education courses, the specificities of this study mode are not effectively present in public policies for initial teacher training.